The Effect of the Relating, Experiencing, Applying, Cooperating, Transferring (REACT) Learning Model on Students' Science Process Skills on Elasticity Topic - Anggiani Anggiani; Nana Nana; Yanti Sofi Makiyah (Berkala Ilmiah Pendidikan Fisika, 2023)
This research is motivated by the lack of science process skills in physics learning. This is seen from the average percentage of science process skills of 31.25% in the lower category. To overcome these problems by using the REACT learning model that emphasizes direct experience in learning to improve students ' science process skills. This study aims to determine the effect of REACT learning model on students ' science process skills on the elasticity topic. The methods in this study are quasi-experiments, posttest-only control design research design, and sampling techniques in the form of random cluster sampling. The instrument used is a test instrument in the form of a question description. The analysis technique test uses a normality test and the homogeneity test, and then the hypothesis test uses a t-test. The results of the hypothesis with the t-test showed that after applying the REACT learning model, 4.49 > 2.385 tcount > ttable is obtained so that H0 is rejected with a significant level (α=0.01). According to the research findings, students' science process skills receive an average score of 86% in the "very good" category after being applied to the REACT learning model. This demonstrates that using the REACT learning model has an impact and can help students improve their science process skills.